The effect of morbid obesity on the outcome of COVID-19 in a child - V. V. Sokolovskaya; A. A. Litvinova; A. V. Krikova; R. S. Kozlov (LLC "Diagnostics and Vaccines", 2022)
Numerous works of domestic and foreign colleagues have proved that obesity is an independent risk factor for severe COVID-19 among patients of all age groups. Of particular interest is the study of the effect of overweight on the course of a new coronavirus infection in children and adolescents.Objective. Demonstration of a clinical case of fatal outcome of COVID-19 in a patient with morbid obesity; analysis and generalization of current data on the effect of obesity on the course of a new coronavirus infection in pediatric patients.The article presents a general understanding of the pathogenetic relationship between the two pathologies, as well as a case of a fatal outcome of a new coronavirus infection in a 9-year-old 4-month-old girl with morbid obesity (BMI - 39 kg/m2, SDS BMI +4.98σ). Emphasis is placed on the lack of parallelism between the results of the procalcitonin test and the development of the septic process.Conclusion. Studies of domestic and foreign colleagues, as well as the clinical case we have cited, confirm that morbid obesity is a risk factor for the adverse course of COVID-19 in children.